Pengaruh Citra merek, Brand Awarenness dan Kepercayaan Merek Terhadap Loyalitas merek pada Pengguna E-Commerce - Latifah, Ummi; Hadi, Wahyu Nofiyan; Wilda, Anisa Nurul (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
This study aims to determine the efect of brand image, brand awareness, brand trust and brand loyalty of E-Commerce costumers. This study used 35 sample respondents using a simple random sampling technique, namely a saturated sampling technique. Testing was carried out using the SPSS ver 23 application which consists of Data Quality Test, Classical Assumptions, Multiple Liner Analysis, Determinant Coefficients and Hypothesis testing. The results of the research show that the results of the t test (partial) show that there is a positive and significant influence of the variables Brand Image, Brand Awareness, and Brand Trust on Brand Loyalty. Of the three research variables, the dominant influence is the Brand Image variable because it has the largest beta coefficient value than the Brand Awareness and Brand Trust variables. The results of this research can be used to develop all e-commerce in the upcoming Keyword : Brand Image, Brand Awareness, Brand Trust And Brand Loyalty